Impact of palm oil and extracted fish meal on haematological parameters, serum constituents and histology of African catfish (Heterobranchus longifilis) fingerlings - Olayiwola Babalola, Theophilus; Friday Apata, David (Scientific Journal of Review, 2012)
This experiment was carried out to determine the effects of supplementing feed with palm oil and extracted fish meal on the histological, haematological and serum biochemical profile of Heterobranchus longifilis. Ten experimental diets were formulated by replacing fish oil with palm oil (PO) at 0, 25, 50, 75 or 100% in extracted and unextracted fishmeal-based diets in a 2 x 5 factorial design. The red blood cell counts (RBC) were significantly affected by the PO levels and highest in fish fed 50% and 75% FO replacement with PO. Extraction of fishmeal significantly affected the haematological parameters. Total protein, glucose concentrations, AST and ALT activities were not significantly (P > 0.05) affected by the PO levels. However, serum total cholesterol was significantly (P < 0.05) increased in fish fed 50% FO. Similarly HDL was significantly (P < 0.05) higher in fish fed 50%, 75% and 100% FO replacement with PO, but HDL of fish fed unextracted fishmeal diets was significantly (P < 0.05) lower than those fed the extracted fishmeal diets. Histological examination of the intestines showed no accumulation of lipid vacuoles in the cytoplasm. However, liver from fish fed unextracted fish meal-based diets with 25%, 50%, 75% and 100% FO replacement showed homogenous size hepatocytes with vacuolized cytoplasm, swelling and nuclei displacement were also evident. These results indicate that extraction of fishmeal and use of PO as a substitute for FO in the diets of H. longifilis had no noticeable negative health impacts.